2010
DOI: 10.1271/bbb.100543
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Pesticides in a Distilled Spirit of Barley Shochu during the Distillation Process

Abstract: Moromi (the fermented mash) of ''mugi shochu'' that had been artificially contaminated with pesticides was distilled to elucidate the fate of pesticides in the distillation process. The pesticides residing in the distillate were quantified by liquid chromatographytandem mass spectrometry (LC-MS/MS). Of the analyzed pesticides (249 compounds), 89% were not detected in the distillate, showing that the distillation process minimized the risk of pesticide contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Meanwhile, in response to increasing consumer demands for food safety, brewers have to present any risks based on experimental data. 4,5) In this study, a traditional Japanese distilled alcoholic beverage, barley shochu, was observed under two distillation processes: distillation under atmospheric pressure and under reduced pressure. Concentrations of each mycotoxin that transferred to the distillates and that remained in the distillation residues were determined by LC-MS/MS.…”
mentioning
confidence: 99%
“…Meanwhile, in response to increasing consumer demands for food safety, brewers have to present any risks based on experimental data. 4,5) In this study, a traditional Japanese distilled alcoholic beverage, barley shochu, was observed under two distillation processes: distillation under atmospheric pressure and under reduced pressure. Concentrations of each mycotoxin that transferred to the distillates and that remained in the distillation residues were determined by LC-MS/MS.…”
mentioning
confidence: 99%
“…In addition, the migration degrees during distillation are dependent on the physicochemical properties of the pesticide because the DMR of flutolanil with the largest amount of contamination (i.e., 1.27 ppm) was only 0.8%, whereas that of ethoprophos with contamination of 0.35 ppm was 14.3%. Previously, Inoue et al [5] contaminated mash with 249 pesticides including ethoprophos, fenthion, flutolanil, and iprobenfos at a concentration of 50 ng/mL, and distilled the mash under reduced pressure (100 mmHg) at 57 °C. Although most pesticides were not detected in the distillate (40% ethanol), 13.1% and 6.9% of the ethoprophos and terbufos migrated, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Han et al [3] reported the residue levels of five insecticides during the manufacture of sorghum distilled spirits and Cabras et al [4] stated the residual contents of eight fungicides and five insecticides in distilled spirits of wine and associated by-products (i.e., cake and lees). In addition, Inoue et al [5] reported the residual contents of 249 pesticides in distillates. All previous studies concluded that the possibility of contaminating pesticides remaining in distillates or distilled spirits was reduced by the actual distillation process.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found that it could obviously reduce the pesticide residues in distilled spirits. [14,28,29] As shown in Table 3, the residues of lambda-cyhalothrin, beta-cypermethrin, esfenvalerate, pyraclostrobin, and difenoconazole were completely eliminated after distillation, which demonstrated that these pesticides could not transfer to the distilled liquor. However, 0.59% of the initial residues of triadimefon were detected in the primary distilled liquor indicating that a small amount of triadimefon could migrate into the distilled liquor.…”
Section: Methods Validationmentioning
confidence: 99%
“…These results demonstrated that the distillation process was effective for decreasing the pesticide residues in distilled liquor. [28] Processing factors A wide range of RAC are processed before they are consumed. Different food processing technologies result in various changes of pesticide residues in foods.…”
Section: Methods Validationmentioning
confidence: 99%